Establishment of Humanized Mice for the Study of HBV - Lai, Fritz; Wee, Cherry Yong Yi; Chen, Qingfeng (Frontiers in Immunology, 2021)
Viral hepatitis particularly Hepatitis B Virus (HBV) is still an ongoing health issue worldwide. Despite the vast technological advancements in research and development, only HBV vaccines, typically given during early years, are currently available as a preventive measure against acquiring the disease from a secondary source. In general, HBV can be cleared naturally by the human immune system if detected at low levels early. However, long term circulation of HBV in the peripheral blood may be detrimental to the human liver, specifically targeting human hepatocytes for cccDNA integration which inevitably supports HBV life cycle for the purpose of reinfection in healthy cells. Although there is some success in using nucleoside analogues or polyclonal antibodies targeting HBV surface antigens (HBsAg) in patients with acute or chronic HBV+ (CHB), majority of them would either respond only partially or succumb to the disease entirely unless they undergo liver transplants from a fully matched healthy donor and even so may not necessarily guarantee a 100% chance of survival. Indeed, in vitro/ex vivo cultures and various transgenic animal models have already provided us with a good understanding of HBV but they primarily lack human specificity or virus-host interactions in the presence of human immune surveillance. Therefore, the demand of utilizing humanized mice has increased over the last decade as a preclinical platform for investigating human-specific immune responses against HBV as well as identifying potential immunotherapeutic strategies in eradicating the virus. Basically, this review covers some of the recent developments and key advantages of humanized mouse models over other conventional transgenic mice platforms.